Analysis Factor and Its Impact on Online Shop Customer Loyalty Lina Shop Surabaya - Jamhadi; Amrun Rosyid (Journal of Economy, Accounting and Management Science (JEAMS), 2023)
This study aims to analyze the influence of security, electronic word of mouth (e-wom), complaints handling against customer satisfaction, and its impact on customer loyalty online shop Lina Shop Surabaya. Collecting data to support this research using a nonprobability sampling method with a purposive sampling approach to 85 respondents and filling the questionnaire. The method used is SEM. Based on the analysis results, it is concluded that security, e-wom, and complaint handling significantly affect customer satisfaction. E-wom and security have no significant effect on customer loyalty, complaint handling, and customer satisfaction have a significant effect on customer loyalty.